Functional Investigation of Iron-Responsive Microsomal Proteins, including MirC, in Aspergillus fumigatus - Mulvihill, Eoin D.; Moloney, Nicola M.; Owens, Rebecca A.; Dolan, Stephen K.; Russell, Lauren; Doyle, Sean (Frontiers in Microbiology, 2017)
The functionality of many microsome-associated proteins which exhibit altered abundance in response to iron limitation in Aspergillus fumigatus is unknown. Here, we generate and characterize eight gene deletion strains, and of most significance reveal that MirC (AFUA_2G05730) contributes to the maintenance of intracellular siderophore (ferricrocin (FC)) levels, augments conidiation, confers protection against oxidative stress, exhibits an intracellular localization and contributes to fungal virulence in the Galleria mellonella animal model system. FC levels were unaffected following deletion of all other genes encoding microsome-associated proteins. MirC does not appear to play a role in either siderophore export from, or uptake into, A. fumigatus. Label-free quantitative proteomic analysis unexpectedly revealed increased abundance of siderophore biosynthetic enzymes. In addition, increased expression of hapX (7.2 and 13.8 fold at 48 and 72 h, respectively; p < 0.001) was observed in ∆mirC compared to wild-type under iron-replete conditions by qRT-PCR. This was complemented by significantly elevated extracellular triacetylfusarinine C (TAFC; p < 0.01) and fusarinine C (FSC; p < 0.05) siderophore secretion. We conclude that MirC plays an important role in FC biosynthesis and contributes to the maintenance of iron homeostasis in A. fumigatus.